Pd-thickness reduction in electroless pore-plated membranes by using doped-ceria as interlayer. (4th March 2020) - Martinez-Diaz, D.; Alique, D.; Calles, J.A.; Sanz, R.
Abstract: This work presents the use of doped CeO2 particles with palladium as intermediate barrier for the preparation of fully dense Pd films by Electroless Pore-Plating. The use of doped ceria particles instead of non-doped ones clearly helps to reduce the final palladium thickness required to prepare a fully dense membrane over porous stainless steel supports from 15 to 9 μm (average values by gravimetric analyses), thus saving around 40% of total palladium required in the process. Pure hydrogen permeation tests reveal a consequent increase in the H2 flux in the range 15–30%, depending on the operation mode. Thus, a H2 permeance of 6.26·10 −4 mol m −2 s −1 Pa −0.5 at 400 °C and ΔP = 1 bar is reached, maintaining a really high H2 /N2 ideal separation factor (≥10, 000) and an activation energy within the typical range for these type of membranes, Ea = 13.1 kJ mol −1 . Permeation of binary H2 /N2 gas mixtures and the effect of feeding the mixture from the inner or the outer side of the membrane have been also studied. A significant concentration-polarization effect was observed, being higher when the gas is fed from the inner to the outer side of the membrane. This effect becomes more relevant for the membrane prepared with doped CeO2, instead of raw CeO2, due to its lower Pd thickness and higher relative influence of the surface processes. However, it should be emphasized that higher H2 permeance values were obtained for the entire set of experiments when using the Pd-membranes containing doped ceria. Finally, long-term permeation tests for more than 850 h with pure gases at T = 400 °C and ΔP = 1 bar were also carried out, demonstrating a suitable mechanical stability of membranes at these operating conditions. Graphical abstract: Image 1 Highlights: Pd-doped CeO2 as intermediate barrier reduces metal thickness in ELP-PP membranes. Pd film below 10 μm was obtained, saving around 40% metal compared to raw CeO2 . H2 permeace 6.26·10 −4 mol/s m 2 Pa 0.5, αH2/N2 ≥10, 000 and Ea = 13.1 kJ mol −1 were reached. Excellent mechanical stability for long-term permeation tests (850 h at 400 °C).